Counting Closed Orbits for the Dyck Shift - Fahad Alsharari; Mohd Salmi Md. Noorani; Habibulla Akhadkulov (Abstract and Applied Analysis)
The prime orbit theorem and Mertens’ theorem are proved for a shift dynamical system of infinite type called the Dyck shift. Different and more direct methods are used in the proof without any complicated theoretical discussion.